DOT seeks comments on previous regulatory guidance (Western Farm Press, 2011)
Specifically, FMCSA requests public comment on: 1) previously published regulatory guidance on the distinction between interstate and intrastate commerce in determining whether operations of commercial motor vehicles within the boundaries of a single state are subject to FMSCA regulations; 2) the factors that states are...